Characterization of COVID-19 on the elderly in the Ciego de Ávila municipality - Magdeline Francisco Castillo; Maité Padrón Castillo; Yadira Rodríguez Luaces; Dania Herrera Escurdia (Medisur)
Background: due to physiological changes of aging, older adults have an increased risk of getting sick from COVID-19. Objective: to characterize of COVID-19 on the elderly in the municipality of Ciego de Ávila. Methods: a cross-sectional descriptive investigation was carried out that included all confirmed COVID-19 patients over 60 years of age in the municipality of Ciego de Ávila in the period between July 1 and December 31, 2021. The information was obtained based on the epidemiological surveys carried out on confirmed cases, as well as the report and statistical records of the Municipal Hygiene and Epidemiology Unit. The data obtained were summarized in tables and graphs. The ethical principles of the research were complied with. Results: 3215 patients were confirmed. Ages between 60 and 69 years (52.26%), females (53.28%). The months of July and August were the ones with the highest number of reports. The North area had the highest incidence (2327.5 per 100 thousand inhabitants) and mortality was higher in patients aged 80 and over (10.6 per 1000 inhabitants). Conclusions: COVID 19 in the Ciego de Avila municipality had a predominance in the elderly who remain more incorporated into social activities, with higher mortality in those over 80 years of age, being the group with the highest vulnerability to present complications. Useful information was provided for monitoring the indicators and in order to contribute to the reduction of mortality in this vulnerable group.